Effectiveness of RME assisted by story calendar media for elementary school students’ mathematical literacy ability - Nugroho, Femas Anggit Wahyu; Zuliana, Eka; Amaliyah, Fitriyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The fact that students mathematical literacy ability are low is behind the need of learning model and media that are oriented toward mathematical literacy ability. This research aimed to determine the effectiveness of RME assisted by story calendar media in improving the mathematical literacy ability of grade VI students of SDN Plumbungan Pati. This research method used a quantitative pre-experimental type with one group pretest-posttest design, with sample is all grade VI students of SDN Plumbungan which totals 25 students. The results of the N-Gain test showed an increase in students mathematical literacy ability in the medium or quite effective category, while the results of the paired sample t test showed a significant difference in the average of the pretest and posttest. It can be concluded that RME assisted by story calendar media is quite effective in improving the mathematical literacy ability of grade VI students of SDN Plumbungan Pati. This research can be used for learning resources, especially the use of model and media that aim to improve students’ mathematical literacy ability. This research recommends that in the implementation of RME assisted by story calendar media, teachers can be more communicative to guide student learning activities. Teachers can also develop story calendar media on other materials, but still take into account the needs of students.